The Added Value of Crescents on Oxford Classification Score in Risk Stratification of End-stage Kidney Disease in Patients with IgA Nephropathy (Iranian Journal of Kidney Diseases, 2022)
Introduction. Crescents (C) have been recently added to the Oxford classification of IgA nephropathy (IgAN) consisting of mesangial hypercellularity (M), endocapillary hypercellularity (E), segmental sclerosis (S) and tubular atrophy/ interstitial fibrosis (T) (MEST). The aim of the study was to assess the added impact of crescents, on development of end-stage kidney disease (ESKD) in IgAN patients Methods. On-hundred fifteen IgAN patients (76% male, mean age: 37 ± 13 years, mean serum creatinine: 4.0 ± 4.3 mg/dL, mean proteinuria: 3.4 ± 2.5 g/d) were followed for 43 ± 29 months. MEST score was defined according to Oxford classification (M0/M1, E0/ E1, S0/S1). To increase the power, T was defined as T0 ≤ 25% and T1 > 25%. Crescents were defined as C0, “absence” and C1 “at least one” crescent. In sensitivity analysis, the risk of ESKD was estimated at different cut-off levels of at least 10, 20, and 30% crescents. Results. Forty patients (35%) developed ESKD. Among those 14% with at least one crescent, 21 patients (46%) developed ESKD. In 11 patients with C ≥ 30%, 66% and among 57 patients with T1, 60% and in 27 patients with T1 + C1 74% developed ESKD. In adjusted model, only C ≥ 30% (HR = 3.15, 95% CI: 1.15 to 11.00; P = 0.027) and the presence of T1+ C1 (HR = 7.18, 95% CI: 1.90 to 27.10, P = 0.004) were associated with increased risk of ESKD. The median kidney survival was 78.0 months (95% CI: 70.5 to 85.6 months), in patients with T0 + C0 and 32.3 months (95% CI: 19.3 to 45.3 months) in patients with T1 + C1. Conclusion. In this study T ≥ 25%, and the presence of crescents ≥ 30%, were independently associated with increased risk of ESKD. This risk was strongly increased in the combined presence of at least one crescent and T1 ≥ 25%, that predicted a high ESKD rate.  DOI: 10.52547/ijkd.6685